Medição do vazamento de uma câmara de vácuo independentemente do gás de referência escolhido - Azevedo, Lucas Oliveira de (Universidade Federal Rural do Semi-Árido, 2018)
The sealing capacity in a vacuum chamber was evaluated based on a theoretical model with experimental support that initially consists on the measurement of the pressure as a function of time. Firstly, data are collected to atmosphere only by the leakage and then 20, 40, 60, 80 and 100 SCCM flows of reference gasses are also inserted, where for this work were used two gases with different properties: hydrogen and argium, in order to prove the validity of the applied method. Through the experiments it was possible to conclude that the variation of the pressure inside the chamber with time is linear for the medium vacuum pressure range and from the angular coefficients of the graphs obtained by linear regression, it was verified that the method used is valid, given the coherence of the values obtained for the leaks at different residual pressures for both reference gases.
Keywords: Câmara de vácuo; Fluxo de gás ar; Vazamento; Vacuum Chamber; Ar Gas Flow; Leakage; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA